MicroRNA and Pathogenesis of Enterovirus Infection - Bing-Ching Ho; Pan-Chyr Yang; Sung-Liang Yu (Viruses, 2016)
There are no currently available specific antiviral therapies for non-polio Enterovirus infections. Although several vaccines have entered clinical trials, the efficacy requires further evaluation, particularly for cross-strain protective activity. Curing patients with viral infections is a public health problem due to antigen alterations and drug resistance caused by the high genomic mutation rate. To conquer these limits in the development of anti-Enterovirus treatments, a comprehensive understanding of the interactions between Enterovirus and host cells is urgently needed. MicroRNA (miRNA) constitutes the biggest family of gene regulators in mammalian cells and regulates almost a half of all human genes. The roles of miRNAs in Enterovirus pathogenesis have recently begun to be noted. In this review, we shed light on recent advances in the understanding of Enterovirus infection-modulated miRNAs. The impacts of altered host miRNAs on cellular processes, including immune escape, apoptosis, signal transduction, shutdown of host protein synthesis and viral replication, are discussed. Finally, miRNA-based medication provides a promising strategy for the development of antiviral therapy.